An environmentally friendly in situ plasma and anodization method to produce titanium dioxide nanotubes. Issue 1 (17th August 2017) - Ambujakshan, Arun T.; Pringle, Jennifer M.; Chen, Zhiqiang; Corr, Cormac S.; du Plessis, Johan; Hodgson, Peter D.; Dai, Xiujuan J.
Abstract : An environmental friendly route to synthesize titanium dioxide nanotube powder is developed using a semi‐batch reactor set‐up that combines both anodization and the plasma treatment of water. A constant supply of the reactive plasma species, such as nitrate and hydrogen peroxide, in the semi‐batch reactor facilitates the formation of titanium dioxide nanotubes during the anodization of titanium. The results are compared against a conventional batch reactor set‐up that uses the same plasma‐treated water constantly during the anodization, which impacts the quality of the nanotubes produced. The semi‐batch reactor set‐up resulted in the formation of powders of titanium dioxide nanotubes with better physical and chemical qualities than those produced in the batch set‐up. Abstract : Freshly prepared plasma‐treated water is produced using a semi‐batch reactor set‐up and used continuously during the anodization of Ti. The ready availability of reactive plasma species during the anodization results in the formation of larger quantities of TiO2 nanotubes with higher quality compared to the batch set‐up.